Morphological characteristics of Olympic slalom canoe and kayak paddlers - Ridge, B.; Broad, E.; Kerr, Deborah; Ackland, T. (Taylor and Francis Group, 2007)
Sidney and Shephard (1973) were the first to report on the morphology of slalom paddlers and characterized them as having “a substantial standing height and lean body mass, good general muscle development with particular emphasis on the leg muscles”. The purpose of this study was to analyse the morphological characteristics of Olympic slalom kayak and canoe paddlers to determine whether they possess unique physique or structural characteristics that provide an advantage for their sport. Thirty-one male and 12 female slalom paddlers were measured using a battery of 36 anthropometric dimensions in the 15-day period before competition at the 2000 Olympic Games. Male slalom paddlers were older, lighter, shorter, and leaner than previously reported slalom paddlers and had similar height and weight to a reference population of non-athletes. Compared with Olympic sprint paddlers, male slalom paddlers were older, lighter and shorter, and had similar body fat and almost identical proportionality characteristics. Female slalom paddlers were taller, lighter, older, and less fat than those reported previously. They were taller and lighter than the reference population of non-athletes and of similar age and height but lighter and leaner than the Olympic sprint paddlers. While a high brachial index was reported for both male and female slalom paddlers, the Best male paddlers (those ranked in the top 10 placings) were more compact, had smaller proportional hip girth, and showed a tendency for smaller proportional hip breadth but a larger proportional waist girth than the Rest (those not ranked in the top 10 placings). Changes to the technical aspect of the events and to competition rules and the nature and approach to training were explored as possible reasons for some of these differences. We outline the contribution this research makes to talent identification and highlight the need for further research.